Effect of surface roughness on amalgam repair using adhesive systems - Giannini Marcelo; Paulillo Luis Alexandre Maffei Sartini; Ambrosano Gláucia Maria Bovi (Fundação Odontológica de Ribeirão Preto, 2002)
The objective of this in vitro study was to evaluate the effect of three surface treatments and two adhesive systems on the shear bond strength of old and freshly placed amalgam. The results suggested that the intact amalgam showed a significantly higher strength than repaired groups and the strongest repaired specimens were made when the amalgam surfaces were roughened with a diamond bur or microetcher. The adhesive systems showed no significant differences on bond strength with the same superficial texture.